Electrochemical Characterization of Cellulose Acetate Butyrate-Prmutit Composite Membrane in Aqueous Uni-Uni Valent Electrolyte Solutions - Tiwari, A.K.; Sonkar, R.; Tiwari, P.K. (International Journal of Applied Sciences and Biotechnology, 2015)
Co-mixed cellulose acetate butyrate and permutit in a definite composition was prepared and coded as MRS-2. The membrane potential was measured with uni-uni valent electrolyte, NaCl solutions using saturated calomel electrodes (SCEs).The effective fixed charge density of the membrane was determined by TMS method and it showed dependence on the porosity, charge on the membrane matrix, charge and size of permeating ions. Other important electrochemical parameters were calculated. Conductance-time data were generated for the kinetic study of the permeating ions in terms of membrane permeability, flow and flux parameters. Donnan membrane equilibrium condition was examined. Membrane adsorbability showed concave dependence with external electrolyte solution and convex type dependence was showed by swelling and conductance parameters. This membrane had no characteristic of anomalous osmosis, indicates that there is no water flooding will take place during membrane operation. Int J Appl Sci Biotechnol, Vol 3(2): 337-341 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12748